W poszukiwaniu wiedzy praktycznie użytecznej. O dojrzewaniu glottodydaktyki jako dziedziny akademickiej - Dakowska, Maria (Neofilolog, 2010)
My thesis in this article is that developing glottodidactics as an academic discipline is an optimal program for the field of foreign language learning and teaching, especially considering its prospects of generating practically useful knowledge. I begin by making distinctions between ‘practice’, ‘theory’, and ‘science’ in the context of three stages in the maturation of our field. This is to show the qualitative differences between a) commonsense b) methodology, and c) an academic discipline with the prospect of satisfying social demands for knowledge which is useful in teaching, understood as its own application. Chances of this full-fledged discipline generating such knowledge, however, depend on its success in constituting itself as mirror image of an empirical discipline with an empirical system as its subject matter.